THE ART OF PERFORMANCE ON TRADITIONAL INSTRUMENTS - Nosirov Dilmurod Tursinovich (Journals Park Publishing, 2024)
The performance of traditional musical instruments is a rich cultural practice that encompasses diverse societies around the world. This article explores the nuances of traditional musical instrument performance, exploring its significance, technique, and impact on performers and audiences. Through an analysis structured following the IMRAD format, this study aims to comprehensively understand the artistry and complexities associated with the performance of traditional instruments.
Keywords: Traditional musical instruments, performance, cultural heritage, music, art.